Dark Prince - Book 1 - Feehan, Christine (New York : Avon, 2011)
"He came to her in the night, a predator -- strength and power chiseled his features. The seduction was deep and elemental; he affected her soul. His need. His darkness. His terrible haunting loneliness. Her senses aroused, she craved the dangerous force of his body. Burned for him. And he had only touched her with his mind. She came to him at dawn, his bleakest hour. As the beast raged inside him, threatening to consume him, he vented his centuries-old despair in an anguished cry that filled the waning night. And she answered, a ray of light, piercing his darkness. A beautiful angel. Her compassion, courage, and innocence awakened in him an exquisite longing and tenderness. He knew he must possess her, for only she could tame his savage side and lift the dark shadow from his soul. Apart they were desolate, bereft. Intertwined physically and spiritually, they could heal one another and experience an eternity of nights filled with love."--Authors website.
"With an additional 100 pages of new material"--P. [4] of cover.
Keywords: Psychics; Fiction; Vampires; Fiction; Carpathian Mountains; Fiction; Thrillers (Fiction)